2020
DOI: 10.1093/femsec/fiaa110
|View full text |Cite
|
Sign up to set email alerts
|

A novel PCR-clamping assay reducing plant host DNA amplification significantly improves prokaryotic endo-microbiome community characterization

Abstract: Due to the sequence homology between the bacterial 16S rRNA gene and plant chloroplast and mitochondrial DNA, the taxonomic characterization of plant microbiome using amplicon-based high throughput sequencing often results in the overwhelming presence of plant-affiliated reads, preventing the thorough description of plant-associated microbial communities. In this work we developed a PCR blocking primer assay targeting the taxonomically informative V5-V6 region of the 16S rRNA gene in order to reduce plant DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 73 publications
3
14
0
Order By: Relevance
“…We found that the predominance of plant DNA in crown gall samples led to the low resolution of endophytic bacterial microbiota survey via standard 16S rRNA gene amplicon sequencing due to the co-amplification of chloroplast and mitochondrial sequences. Although the use of 16S rRNA gene primers containing mismatches to 16S rRNA gene of plant chloroplast or mitochondria could potentially reduce host contamination in endophytic microbiota studies (23, 39), the “bacteria-specific” primers did not work well in previous studies (20) and resulted in > 90% host reads of our initial attempt (Round I) (Table 2). When adding blockers that could specifically anneal to chloroplast or mitochondrial DNA but not be extended by DNA polymerase during PCR, we successfully reduced the host contamination and obtained sufficient sequencing depth for this study.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the predominance of plant DNA in crown gall samples led to the low resolution of endophytic bacterial microbiota survey via standard 16S rRNA gene amplicon sequencing due to the co-amplification of chloroplast and mitochondrial sequences. Although the use of 16S rRNA gene primers containing mismatches to 16S rRNA gene of plant chloroplast or mitochondria could potentially reduce host contamination in endophytic microbiota studies (23, 39), the “bacteria-specific” primers did not work well in previous studies (20) and resulted in > 90% host reads of our initial attempt (Round I) (Table 2). When adding blockers that could specifically anneal to chloroplast or mitochondrial DNA but not be extended by DNA polymerase during PCR, we successfully reduced the host contamination and obtained sufficient sequencing depth for this study.…”
Section: Discussionmentioning
confidence: 99%
“…The elucidation of the ubiquitous existence of diverse microorganisms in live plant cells with their continuous vertical transmission opens up scope for further research on spin-off study areas in plant biology similar to the interdependent human- and animal-associated microbiota ( Engel and Moran, 2013 ; Almeida et al, 2019 ). It might be possible to bring out more diversity adopting alternate methods to block the amplification of mitochondrial and plastid sequences, such as the design and the use of PNA PCR clamps ( Lundberg et al, 2013 ; Lefèvre et al, 2020 ). This warrants a comparative study to assess if the two-step QIIME analysis adopted in this study, or the use of PNA clamps harnesses more taxonomic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Tissues were then removed from the tube and the tube was centrifuged at 13000 g for 5 min to obtain a cell pellet. The supernatant was decanted, and DNA was extracted from the resulting pellet using the UltraClean Microbial DNA kit (MoBio Laboratories), according to the manufacturer’s instructions [50]. All extracted DNA was quantified using a Qubit 2.0 fluorometer and stored at −80°C until further analysis.…”
Section: Methodsmentioning
confidence: 99%